Aplikasi Pengukur Berat Badan Ideal Menggunakan Mit App Inventor Berbasis Android - Abel Ratino, Sularno (GLOBAL SCIENTS PUBLISHER, 2024)
This journal presents the development and evaluation of an Ideal Body Weight Calculator Application using MIT App Inventor on the Android platform. The application aims to provide a user-friendly tool for calculating ideal body weight based on established formulas, thereby promoting health awareness and facilitating healthy lifestyle choices. By integrating intuitive design principles and leveraging MIT App Inventor's capabilities, the application offers a seamless user experience. Users input their height and gender into the interface, which then computes and presents the ideal weight range. The study discusses the design methodology, implementation process, and usability evaluation, emphasizing the application's potential in encouraging users to monitor and manage their weight effectively.